Regulação ambiental e desenvolvimento sustentável : um estudo econômico sobre o projeto produtores de água no ES - Gonçalves, Oldair Luiz (2011)
In the context of Environmental Regulation and Sustainable Development this dissertation has as focus the economic study of the potential and limitations of PSA projects, as instruments for promotion of sustainable development in the state of Espírito Santo. It systematizes concepts of growth, economic and sustainable development, environmental regulation, public assets, externalities and theoretic solution proposals. Systematize technical and historical data aiming at identifying the water s role on sustainable development and, finally, synthesizes and analyses the structure and operationalization of the Project "ProdutorES de Água do Espírito Santo", pointing out conclusions as follows: although still very limited in it s capacity and area of coverage, this program has important potential as an instruments sustainable development promotion in the state of Espírito Santo.